Drop-size-dependent effects in leading-edge rain erosion and their impact on erosion-safe mode operation - N. Barfknecht; D. von Terzi (Wind Energy Science)
Leading-edge rain erosion poses a significant challenge for the wind turbine industry due to its detrimental effects on structural integrity and annual energy production. Developing effective mitigation strategies requires understanding the precipitation conditions driving erosion. The influence of the rain droplet diameter on both the formation of erosion damage and erosion mitigation strategies has yet to be sufficiently understood. This study proposes an enhanced damage model based on the impingement metric as used in the state of the art but improved by including important and thus far neglected physical mechanisms such as the recently described droplet slowdown and deformation effect. Several drop-size-dependent effects are identified within the damage model. Subsequently, their significance for leading-edge erosion is established for the International Energy Agency (IEA) 15 MW reference wind turbine, a site in the Netherlands and a commercial leading-edge coating. Thereafter, the influence of the drop-size effects on the viability of the erosion-safe mode (ESM) is investigated. The outcome is that drop-size effects strongly impact the erosion process and should not be neglected during modeling. Large droplets are considerably more damaging than small droplets, even when normalized for water volume. This directly influences the parameter space of erosion, such as the relevant droplet diameter range that should be studied. The drop-size effects shift damage production to higher rain intensities. Roughly half of the erosion damage is produced by only 10 % of rain events. When drop-size effects are excluded, this value shifts to more than 20 %. Regarding the ESM, we found that it can be utilized up to twice as efficiently when drop-size effects are adequately modeled. The findings highlight the criticality of drop-size effects in rain erosion modeling for wind turbine blades, impacting lifetime predictions, ESM viability and the parameter space of leading-edge erosion. This paper also provides a formal derivation of impingement and describes a method for finding optimal ESM strategies.